UPAYA PENINGKATAN PENALARAN MATEMATIS MAHASISWA UNIVERSITAS TRIBHUWANA TUNGGADEWI MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) - Rio Febrianto Arifendi; Rudy Setiawan (Program Studi Pendidikan Matematika, 2019)
This study aims to describe the learning steps by using the Contextual Teaching Learning (CTL) approach that can improve students 'mathematical reasoning, so that students' mathematical reasoning problems are well resolved in the learning process. Classroom Action Research). The research design consists of several actions, one action is called a cycle. The activities of each cycle consist of four main activities, namely planning (planning), action (action), observation (observation), and reflection (reflection). The CTL strategy used in this study includes: Relating, Cooperating, Experiencing, Appliying, Transfering. The results of the study show that: (1) Implementation of learning with an approach consists of: Students observe problems, write problems, solve problems, and students discuss problems; (2) Mathematical reasoning of students who study using CTL has increased; (3) Learning with CTL is favored by students.